2009
DOI: 10.3354/meps08014
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of division rates in coastal dinoflagellate Dinophysis spp. populations: implications for modelling

Abstract: This study explores vertical heterogeneities of in situ division rates (μ) of 3 species of Dinophysis and discusses its implications in modelling the population dynamics of these species. Based on a post-mitotic index approach, estimates of μ from vertical net-haul (integrated) samples (μ int ) were compared with those from a single depth (oceanographic bottle samples) (μ z ) at the cell maximum during 2 daily cell cycle studies in the Galician Rías Baixas (NW Spain). Additionally, vertical profiles of μ z wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…acuminata often exhibits sharp heterogeneities in their vertical distribution (Velo-Suá rez et al, 2008). Factors such as advection, usually described as the most important factor in dinoflagellate accumulation during downwelling conditions, and in situ growth, may have caused an increment in D. acuminata concentrations as observed by Velo-Suá rez et al (2009). Others researchers have suggested that the diurnal variability observed in Dinophysis spp.…”
Section: Tide Effect On the Diel Variability Of D Acuminatamentioning
confidence: 85%
“…acuminata often exhibits sharp heterogeneities in their vertical distribution (Velo-Suá rez et al, 2008). Factors such as advection, usually described as the most important factor in dinoflagellate accumulation during downwelling conditions, and in situ growth, may have caused an increment in D. acuminata concentrations as observed by Velo-Suá rez et al (2009). Others researchers have suggested that the diurnal variability observed in Dinophysis spp.…”
Section: Tide Effect On the Diel Variability Of D Acuminatamentioning
confidence: 85%
“…Several species of Dinophysis have been observed to exhibit in phase cell division in field populations from different temperate regions (Campbell et al, 2010;Farrell et al, in press-b;Velo-Suá rez et al, 2009 and references therein). Cell division is maximal in early morning.…”
Section: In Situ Growth: Slow Growers or Amazing Survivors?mentioning
confidence: 94%
“…have been considered slow-growers by some authors (Smayda and Reynolds, 2001;Stolte and Garcé s, 2006). Nevertheless, field observations have shown that different species of Dinophysis observed during different stages of their population growth and under distinct environmental conditions can exhibit a wide range of values in m gross , between practically zero and as high as 1 division per day (m gross = 0.69 d À1 ) (see Table 1 in Velo-Suá rez et al, 2009;Farrell et al, in press-b). Therefore, in field conditions Dinophysis spp.…”
Section: In Situ Growth: Slow Growers or Amazing Survivors?mentioning
confidence: 95%
“…Further, in the case of Dinophysis spp., that usually constitute only a small (<5%) percentage of the microplankton assemblage, bulk measurements using chemical indicators, such as chlorophyll a concentration or primary production, and conventional cell counts, are unsuitable to follow the bloom dynamics (Reguera et al, 2003;Velo-Suá rez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%